Circumcising the body: negotiating difference and belonging in Germany. Issue 2 (14th March 2020) - Dekel, Irit; Forchtner, Bernhard; Efe, Ibrahim
ABSTRACT: The circumcision debate in Germany in 2012 is an exemplary case for symbolic struggles over national boundaries. The debate became a site for the negotiation of traditions practiced by religious minorities. We ask, first, how the clinical gaze constitutes Muslim and Jewish others. Second, we investigate how 'writing around' the debate's center, bodily integrity, became meaningful through analogies to other practices said to harm it. We compare newspaper coverage in Germany, Israel and Turkey, and reveal transnational discursive dynamics that transgress national boundaries. We show how 'otherness' of Muslims and Jews remains present in a self-perceived secular, liberal imaginary.